2007
DOI: 10.1007/s00192-007-0513-7
|View full text |Cite
|
Sign up to set email alerts
|

The surgical anatomy of rectocele and anterior rectal wall intussusception

Abstract: The aim of the study was to analyse the dynamic anatomical supports of the posterior vaginal wall from the perspective of rectocele and rectal intussusception repair. Two groups of patients were studied. Group 1 (n = 24) with genuine stress incontinence but no major vault prolapse had vagino/proctomyograms and transperineal ultrasound examinations. Group 2 with vaginal vault prolapse, clinical rectoceles and obstructive defecation symptoms (n = 19 had single-contrast defecating proctography before and after po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Our surgical measurement included the STP and DTP muscles, whereas Zetterstrom et al [2] measured the PB by ultrasonography as the distance between the inner surface of the internal anal sphincter and the reflection of a finger held gently against the posterior vaginal wall. Using radiological methods, Abendstein et al [1] reported that the PB formed more than 50% of the support of the posterior vaginal wall; however, they did not specify the actual length of the PB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our surgical measurement included the STP and DTP muscles, whereas Zetterstrom et al [2] measured the PB by ultrasonography as the distance between the inner surface of the internal anal sphincter and the reflection of a finger held gently against the posterior vaginal wall. Using radiological methods, Abendstein et al [1] reported that the PB formed more than 50% of the support of the posterior vaginal wall; however, they did not specify the actual length of the PB.…”
Section: Discussionmentioning
confidence: 99%
“…The supportive role of the perineal body (PB) is well documented. Using X-ray and evacuating proctogram studies, Abendstein et al [1] demonstrated that the PB structures support at least 50% of the posterior vaginal wall. Using an ultrasound technique limited to the axial plane, Zetterstr€ om et al [2] found that the PB measured only 12 AE 3 mm in asymptomatic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…When uterosacral/cardinal ligaments stretch or levator muscles weaken through direct injury, avulsion, or neuromuscular damage from obstetrical trauma, excessive force may be placed on the rectovaginal septum leading to attenuation and/or discrete breaks and posterior vaginal compartment prolapse [22][23][24].…”
Section: Anatomymentioning
confidence: 99%
“…A self‐administered questionnaire is less intimidating for the patient and is more sensitive [9]. Finally, the postoperative benefit for continence may be overestimated in studies offering a follow‐up that is too short [5].…”
Section: Introductionmentioning
confidence: 99%